Da’wah in Household Product Advertisements: A Reception Study of Islamic Values in Nawaitu Sahaja TV Advertisements - Rahmania Santoso; Desi Dwi Prianti (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2022)
In Indonesian contemporary society, spirituality and religion can be used to create Islamic brand identities. In order to promote the intended identity, marketers use advertisements to reach their target audience. Sahaja, an Indonesian brand of home care products, uses Islamic identity as part of their strategic communication. Using their Nawaitu Sahaja advertisements, they promote the da’wah (promotion of Islam) message. This research aimed to examine how a Muslim audience receives the Islamic da’wah used by Nawaitu Sahaja. To understand how audiences, receive the Islamic values portrayed in the Nawaitu Sahaja advertisements, seven women who are part of Nasyiatul Aisyiyah – an Islamic women’s organis ation – were interviewed in 2021. In order to promote their products, Nawaitu Sahaja advocates the importance of making a clean and hygienic home as part of one’s Islamic values. Baiti Jannati (